Global Lysine Crotonylation Alterations of Host Cell Proteins Caused by Brucella Effector BspF - Zhu, Jinying; Dong, Qiao; Dong, Changpeng; Zhang, Xi; Zhang, Huan; Chen, Zeliang (Frontiers in Cellular and Infection Microbiology, 2021)
In Brucella spp., the type IV secretion system (T4SS) is essential for bacterial intracellular survival and inhibition of the host innate immune response. The Brucella T4SS secretes 15 different effectors to escape host immunity and promote intracellular replication. Among them, BspF has a GNAT-family acetyltransferase domain, implying its acetyltransferase activity. To test this, in this study, we first tested and confirmed that BspF has de-histone crotonyltransferase activity in vitro. Unexpectedly, we also found that BspF enhances histone crotonylation of host cell proteins. We then conducted enrichment of crotonylated proteins and used LC-MS to study the crotonylation of proteins in HEK-293T cells caused BspF overexpression. A total of 5,559 crotonylation sites were identified on 1,525 different proteins, of which 331 sites on 265 proteins were significantly changed 30 h after transfection. Among these differentially modified proteins, a significant proportions were involved in immune response and defense mechanism. We propose that BspF may influence the function of these host proteins by changing the level of crotonylation, thereby promoting the intracellular propagation of Brucella.